2013
DOI: 10.1002/ar.22564
|View full text |Cite
|
Sign up to set email alerts
|

Hyperostosis in Three Fish Species Collected From the Sea of Oman

Abstract: Hyperostotic conditions are described in three teleost fishes. Pomadasys stridens, (Haemulidae; 326 mm TL, 314 mm SL), Drepane longimana (Drepanidae; 450 mm, TL, 440 mm SL), and Platax teira (Ephippidae) captured off the coast of Muscat City. There are regions of hyperostosis in four bones in P. stridens, three in D. longimana and seven in P. teira. Size, shape, position, and species‐specific characteristics showed wide variation in these three species. © 2013 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In the studies mentioned above, the hyperostosis was larger structures than the presently observed calluses. Interestingly, hyperostosis has also been reported with similar size and macroscopic shape as the calluses reported herein (Jawad, ), and in both haemal (Gauldie & Czochanska, ) and neural (Jawad & Bannai, ) spines.…”
Section: Discussionsupporting
confidence: 85%
“…In the studies mentioned above, the hyperostosis was larger structures than the presently observed calluses. Interestingly, hyperostosis has also been reported with similar size and macroscopic shape as the calluses reported herein (Jawad, ), and in both haemal (Gauldie & Czochanska, ) and neural (Jawad & Bannai, ) spines.…”
Section: Discussionsupporting
confidence: 85%
“…The distinct appearance of the strip may indicate that a fracture has induced the hyperostosis, and that the excessive bone deposition may be a mechanism to stabilize the haemal spine, or a stage in a fracture repair mechanism, involving callus formation and remodelling into normal morphology (discussed in Fjelldal et al., ). Excessive bone deposition in fish has earlier been termed calluses (Fjelldal et al., ), hyperostosis (Gauldie & Czochanska, ; Jawad, ; Jawad, Wallace, & Dyck, ; Smith‐Vaniz, Kaufman, & Glowacki, ), and osteomas (Lima, Souza, Mesquita, Souza, & Chinelli, ), and probably reflects a variety of pathological and un‐pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…). The hyperostotic bone appears externally swollen in appearance, though histological examination reveals that only the periosteum shows increased ossification, while the remaining cellular tissue undergoes resorption resulting in only trabecular bone remaining (Meunier & Desse, ; Jawad, ). In fishes, hyperostosis is a localized area of osteocytic bone, within an otherwise anosteocytic skeletal element (Smith‐Vaniz et al.…”
Section: Introductionmentioning
confidence: 99%
“…Representative examples of hyperostosis in fishes indicated in red. (A) Hyperostosis in Drepane longimana (modified from radiograph available on Australian Museum, http://australianmuseum.net.au/image/hyperostosis-in-a-banded-sicklefish; Jawad, ). (B) Alectis alexandrinus (modified from Smith‐Vaniz et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation